PAK GANJAR (PAKET KOMPRES ICE GELL AROMATERAPI DAN JAM MUSIK RELAKSASI) MENGURANGI CEMAS DAN NYERI PADA ANAK USIA PRASEKOLAH SELAMA PEMASANGAN INFUS - Agung Laksana Hendra Pamungkas; Sukirno; Galuh Yunawan Riyadi (Jurnal Ilmu Keperawatan Anak, 2023)
The purpose of this study was to analyze the effectiveness of Pak Ganjar application in reducing the intensity of pain and anxiety in pre-school-aged children when infusions were placed at Harapan Anda Hospital in Tegal City. This research is a quantitative study with a post-test with control group design. The sample of this study were 66 children who were given an infusion at the Harapan Anda Hospital in Tegal City. Measurement of pain using the Face, Leg, Activity, Cry and Consolability (FLACC) method and measuring anxiety using The Hamilton Anxiety Rating Scale (HARS) Data analysis used univariate analysis and bivariate analysis with an approach using the Wilcoxon test. The results of the study proved that statistically the Asymp sig value was 0.000 <0.05, which means that there was a difference between the control and intervention groups. This means that there is a significant effect of Pak Ganjar intervention on reducing the intensity of pain and anxiety during infusion at RSU Islam Harapan Anda, Tegal City.